Influences of Dietary and Environmental Stress on Microbial Populations in the Murine Gastrointestinal Tract - Tannock, Gerald W. (1974)
Aerobic and anaerobic cultural techniques and histological methods were used in a study of the effects of environmental and dietary stress on the indigenous microbiota of the gastrointestinal tract of mice. Mice previously inoculated with Salmonella typhimurium were examined in a similar manner. Three strains of mice (CD-1, Ha/ICr, and C57BL) were used. Control animals previously inoculated with S. typhimurium had low population levels of Salmonella bacteria in the small and large bowel. Mice previously inoculated with Salmonella and then deprived of food, water, and bedding for 48 h harbored high population levels of these bacteria in their small and large bowels. Coliforms increased in numbers in the large bowel of stressed mice inoculated with Salmonella and in the jejunum-ileum and cecum of stressed mice not previously inoculated with Salmonella. Control mice had high population levels of lactobacilli inhabiting the keratinized squamous epithelium of the stomach. Stressed mice showed dramatic reductions in these populations of lactobacilli. Populations of fusiform-shaped bacteria associated with the mucosal epithelium of the cecum and colon in control mice were reduced in stressed mice as determined by microscope examination of histological sections. Total anaerobic counts were similar, however, in both stressed and control animals. Environmental and dietary stress markedly alter the gastrointestinal microbiota in mice. Therefore, such stressful conditions profoundly affect the factors that regulate the localization and population levels of microorganisms in the stomach and intestines.